Direct RIG‐I activation in human NK cells induces TRAIL‐dependent cytotoxicity toward autologous melanoma cells. Issue 7 (9th January 2019) - Daßler‐Plenker, Juliane; Paschen, Annette; Putschli, Bastian; Rattay, Stephanie; Schmitz, Saskia; Goldeck, Marion; Bartok, Eva; Hartmann, Gunther; Coch, Christoph
Abstract : Activation of the innate immune receptor retinoic acid‐inducible gene I (RIG‐I) by its specific ligand 5′‐triphosphate RNA (3pRNA) triggers anti‐tumor immunity, which is dependent on natural killer (NK) cell activation and cytokine induction. However, to date, RIG‐I expression and the functional consequences of RIG‐I activation in NK cells have not been examined. Here, we show for the first time the expression of RIG‐I in human NK cells and their activation upon RIG‐I ligand (3pRNA) transfection. 3pRNA‐activated NK cells killed melanoma cells more efficiently than NK cells activated by type I interferon. Stimulation of RIG‐I in NK cells specifically increased the surface expression of membrane‐bound TNF‐related apoptosis‐inducing ligand (TRAIL) on NK cells, while activated NK cell receptors were not affected. RIG‐I‐induced membrane‐bound TRAIL initiated death‐receptor‐pathway‐mediated apoptosis not only in allogeneic but also in autologous human leukocyte antigen (HLA) class I‐positive and HLA class I‐negative melanoma cells. These results identify the direct activation of RIG‐I in NK cells as a novel mechanism for how RIG‐I can trigger enhanced NK cell killing of tumor cells, underscoring the potential of RIG‐I activation for tumor immunotherapy. Abstract : What's new? Activation of the innate immune receptor RIG‐I triggers anti‐tumor immunity, which is dependent on natural killer (NK) cell activation and cytokine induction. However, a mechanism explaining how RIG‐I activates NK cells remains elusive. Our study demonstrates that naïve NK cells express RIG‐I and are activated upon RIG‐I ligand transfection. RIG‐I activation induces TRAIL expression on NK cells, which, in turn, induces cell death in melanoma cells. TRAIL‐dependent killing via RIG‐I is induced not only in allogeneic but also in autologous melanoma cells. Direct RIG‐I activation in NK cells thus emerges as a novel, hitherto unappreciated, functional component of RIG‐I‐mediated immunotherapy.